2013
DOI: 10.1089/vbz.2011.0954
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships of the Spinolai Complex and Other Triatomini Based on Mitochondrial DNA Sequences (Hemiptera: Reduviidae)

Abstract: In this study, we performed a phylogenetic analysis of 35 species of the tribe Triatomini by means of available 16S ribosomal DNA and cytochrome b (Cyt b) gene sequence data, adding taxa of the spinolai complex, to clarify phylogenetic relationships of this complex and related triatomines. The phylogenetic analysis suggests a monophyletic clustering of the spinolai complex related to the South American species of triatomines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The correlations between these markers have been verified in triatomines (Dujardin et al 1999, Villegas et al 2002, Martínez-Hernández et al 2010, Ceballos et al 2011, Villacís 2011) and other medically important insects , Bouyer et al 2007). In some cases, the phenotypic differences observed in triatomines (Moreno et al 2006) have been subsequently corroborated with genetic markers (Campos et al 2012). Moreover, Villacís (2011) showed greater microgeographic differentiation of Rhodnius ecuadoriensis populations when antennal phenotypes were used instead of microsatellite markers.…”
Section: Discussionmentioning
confidence: 89%
“…The correlations between these markers have been verified in triatomines (Dujardin et al 1999, Villegas et al 2002, Martínez-Hernández et al 2010, Ceballos et al 2011, Villacís 2011) and other medically important insects , Bouyer et al 2007). In some cases, the phenotypic differences observed in triatomines (Moreno et al 2006) have been subsequently corroborated with genetic markers (Campos et al 2012). Moreover, Villacís (2011) showed greater microgeographic differentiation of Rhodnius ecuadoriensis populations when antennal phenotypes were used instead of microsatellite markers.…”
Section: Discussionmentioning
confidence: 89%
“…() for M. spinolai , and because M. gajardoi is a close species to M. spinolai and part of the Spinolai complex as suggested by Campos et al . (, ), this species could also delay defaecation on hosts, which would make it a less‐efficient vector under natural conditions. However, the feeding behaviour of M. gajardoi has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported by Canals et al (1999) for M. spinolai and T. infestans suggest that because of the differences in their defaecation behaviour once they feed on their hosts, T. infestans would be a better vector than M. spinolai that takes more time to release their droppings, whereas T. infestans do so immediately. When considering the results of Canals et al (1999) for M. spinolai, and because M. gajardoi is a close species to M. spinolai and part of the Spinolai complex as suggested by Campos et al (2013aCampos et al ( , 2013b, this species could also delay defaecation on hosts, which would make it a less-efficient vector under natural conditions. However, the feeding behaviour of M. gajardoi has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…7 Mepraia gajardoi is a genetically related triatomine described as a separate species from M. spinolai. It has similar feeding behavior and is distributed along the northern coast of Chile between 18 S and 21 S. 8,9 Blood meal analyses from an insular population of M. spinolai from the southern Pacific Ocean coast of Chile (26 S) showed that coastal populations feed on seabirds, marine mammals, and reptiles. 10 The purpose of this study was to determine T. cruzi genotypes in M. gajardoi from wild ecotopes of northern Chile.…”
mentioning
confidence: 99%